2019
DOI: 10.1097/mej.0000000000000503
|View full text |Cite
|
Sign up to set email alerts
|

Do prehospital providers and emergency nurses agree on triage assignment?: an efficacy study

Abstract: There was a moderate interrater agreement on triage assignment between ED nurses and prehospital providers. They agreed on final triage more often if they agreed on triage based on vital signs rather than presenting complaints.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Studies of RETTS-A (ED) have reported that increased mortality and inhospital stay were associated with a higher triage level, with an ED nurse inter-reliability of moderate to good [11,12]. Studies of the Danish emergency process triage (DEPT), the Canadian triage and acuity scale (CTAS), and the emergency severity index (ESI) have reported only moderate agreement between EMS clinicians and ED nurses when utilising identical triage systems [13][14][15]. RETTS-A was not developed to be utilised as a system assessing whether low-acuity patients should stay at the scene with self-care or referral to PC.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of RETTS-A (ED) have reported that increased mortality and inhospital stay were associated with a higher triage level, with an ED nurse inter-reliability of moderate to good [11,12]. Studies of the Danish emergency process triage (DEPT), the Canadian triage and acuity scale (CTAS), and the emergency severity index (ESI) have reported only moderate agreement between EMS clinicians and ED nurses when utilising identical triage systems [13][14][15]. RETTS-A was not developed to be utilised as a system assessing whether low-acuity patients should stay at the scene with self-care or referral to PC.…”
Section: Introductionmentioning
confidence: 99%
“…5 Several methods are used worldwide to assess and prioritise (triage) patients in the chain of emergency care. [6][7][8] Examples are the Manchester Triage Scale, the Australasian Triage Scale, the Canadian Triage and Acuity Scale and the South African Triage Scale (SATS). [9][10][11][12][13] Effective triage should rapidly identify patients with life-threatening conditions in need of immediate care and ensure that each patient receives similar initial assessment, facilitating further diagnostic work-up and treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Currently all countries face increase in the number of patients visiting emergency departments, which provide them with primary access to a health care system [1]. This situation is explained by the lack of clinical guidelines developed for management of emergency pathologies at the preclinical stage [2]. The number of patients admitted to emergency departments cannot be predicted with great precision; and only a fraction of those suffers from lifethreatening diseases or conditions requiring urgent care [3], and not all patients are in need of immediate medical care.…”
Section: Introductionmentioning
confidence: 99%